The influence of job motivation and work environment upon job performance of the employees of trade and industry office in Bogor district - Sumardjono Sumardjono; Rizki Adiatama (The Management Journal of Binaniaga, 2019)
This study aims to explain the effect of job motivation and work environment upon job performance of the employees of Trade and Industry Office in Bogor District. The analytical instrument used in this study is Multiple Linear Regression which is first test using validity and reliability tests. The data analysis technique used in this study is using SPSS 22.0 computer statistical software. The sampling method taken is 121 respondents. The results of this study indicate that Job Motivation has a significant effect on job performance of the employees of (Dinas Perdagangan dan Perindustrian Kabupaten Bogor) Trade and Industry Office in Bogor District, Work Environment has no significant effect on the job performance of the employees of Trade and Industry Office in Bogor District. Job Motivation and Work Environment simultaneously does not affect job performance of the employees of Trade and Industry Office in Bogor Office. Keywords: Job Motivation, Work Environment, Employees Job Performance